2014
DOI: 10.1210/jc.2013-3487
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome Due to Malignant Hypercalcemia: Physiopathological Considerations

Abstract: The development of PRES in the setting of severe hypercalcemia is extremely rare. Hypercalcemia could lead to PRES in the absence of hypertension by various mechanisms, including vasospasm, endothelial dysfunction, and an inflammatory state. A high index of suspicion is needed in this setting because hypercalcemia can lead to neurological symptomatology, and prompt diagnosis is essential for adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…Hypercalcemia has been associated with numerous neurological symptoms including weakness, fatigue, confusion, and coma. Previous studies have reported the association of hypercalcemia with RCVS or PRES, but not both concurrently . RCVS and PRES share many clinico‐radiological features, which are typically reversible with prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia has been associated with numerous neurological symptoms including weakness, fatigue, confusion, and coma. Previous studies have reported the association of hypercalcemia with RCVS or PRES, but not both concurrently . RCVS and PRES share many clinico‐radiological features, which are typically reversible with prompt diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia has been described in infants with congenital lactase deficiency 81 ; the hypercalcemia may be due to an increase in calcium absorption in the ileum in the presence of non-hydrolyzed lactose, and it resolves rapidly after the institution of a lactose-free diet. Recently, hypercalcemia was reported to be associated with posterior reversible encephalopathy syndrome in a 38-year-old woman who presented with altered mental status 82 . Factors increasing bone resorption, including immobilization, Paget's disease and the administration of estrogen, can cause hypercalcemia 4,18,34 .…”
Section: Other Rare Conditionsmentioning
confidence: 99%
“…The number of associated conditions with PRES has increased although hypertension remains the most common, as well as renal disease, sepsis and immunosuppressive drug use. 8 Hypercalcemia is an extremely rare cause of PRES. 9 We report the case of PRES associated with a hypercalcemic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Neurologic manifestations are mainly cognitive and neuromuscular in nature and range from personality changes, to lack of concentration, memory impairment, and, in severe cases, lethargy and coma. 12 Other rarely reported neurologic manifestations include PRES.…”
mentioning
confidence: 99%
See 1 more Smart Citation